A case of acute limb ischemia - Rai, Kshiti; Kumar, K. G. Sajeeth; Ekkalayil, Danish; K., Anoop Chanthu K. (International Journal of Advances in Medicine, 2021)
Thromboembolism is a well-recognized complication of hematological malignancy. The incidence of symptomatic thrombosis at diagnosis is relatively low in AML (acute myeloid leukemia) patients, though its incidence increases on treatment with anthracyclines. We reported a case of 69 year old female with T2DM who presented with DVT and later on acute limb ischemia of the same lower limb. On hematological evaluation, she had leukocytosis and thrombocytopenia. Further evaluation revealed AML. Thromboembolism as a rare presentation of AML in adults with leukemic hyperleukocytosis has seldom been reported. In the absence of clear guidelines, early diagnosis and management are desirable.